Copertura delle retribuzioni e inflazione a tasso variabile (Coverage of wages and inflation rate variable) - R. FILOSA; I. VISCO (Moneta e Credito, 2014)
In his latest work on indexing of wages L. Spaventa critically reviewed various contributions with the aim of both reiterating some of his previous conclusions and extending the analysis. In particular, he has taken some of the authors’ conclusions on the dynamic behavior and the criteria for measuring the degree of coverage of wages which, in his opinion, are incorrect. With the present note, the authors respond to these criticisms, presenting a further contribution on the development of coverage and the real wage during the acceleration or deceleration of prices.